2020
DOI: 10.20945/2359-3997000000217
|View full text |Cite
|
Sign up to set email alerts
|

Determining an optimal cut-off value for follicle-stimulating hormone to predict microsurgical testicular sperm extraction outcome in patients with non-obstructive azoospermia

Abstract: Objective: To determine the optimal cutoff value for follicle stimulating hormone (FSH) to predict the outcome of microsurgical testicular sperm extraction (micro-TESE) in patients with nonobstructive azoospermia (NOA). Subjects and methods: We included a total number of 180 patients with NOA. The serum level of FSH was determined and all the subjects underwent micro-TESE. We determined the optimal cutoff value for FSH and assessed whether the test could be effectively used as a successful predictor of sperm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…57 A retrospective study of 180 patients who NOA who underwent MD-TESE showed that the mean serum FSH level was significantly higher in the failure group than in the success group (p < 0.001), and a plasma FSH level > 14.6 mIU/mL predicted failure of sperm retrieval. 58 In contrast, in our study, we found that the mean serum FSH level was significantly higher in the success group than in the failure group (p = 0.001). 14 We also found that a plasma FSH level > 19.01 mIU/mL was the best cutoff value for predicting the SRR in patients with NOA.…”
Section: Factors Predicting the Srr In Patients With Noa Before Surgerycontrasting
confidence: 87%
“…57 A retrospective study of 180 patients who NOA who underwent MD-TESE showed that the mean serum FSH level was significantly higher in the failure group than in the success group (p < 0.001), and a plasma FSH level > 14.6 mIU/mL predicted failure of sperm retrieval. 58 In contrast, in our study, we found that the mean serum FSH level was significantly higher in the success group than in the failure group (p = 0.001). 14 We also found that a plasma FSH level > 19.01 mIU/mL was the best cutoff value for predicting the SRR in patients with NOA.…”
Section: Factors Predicting the Srr In Patients With Noa Before Surgerycontrasting
confidence: 87%
“…Consistent with our results, some preliminary studies of patients with NOA have reported no significant differences in TV or hormonal levels based on the success or failure of micro-TESE ( 32 , 33 ). Accordingly, serum hormone levels were not identified as a significant predictor of successful SRO ( 34 ). However, some studies have reported significantly higher levels of serum FSH in the failed group than in the successful group.…”
Section: Discussionmentioning
confidence: 94%
“…High levels of FSH and LH have been suggested as a contributing factor of abnormality in spermatogenesis, a cause of NOA, by multiple studies [5,[10][11][12]. Te study by Jahromi et al has even suggested FSH plasma levels above 14.6 mIU/mL as a failure predictor of micro-TESE in NOA patients [5], while another study associated elevated FSH and LH with failed sperm retrieval [13]. Elevated FSH/LH levels combined with other factors such as varicocele and chromosomal abnormalities are indicators of hypergonadotropic hypogonadism/eugonadism [12].…”
Section: Discussionmentioning
confidence: 99%
“…Tis can result in impaired sperm production. Te assessment of testicular function by the measurement of serum gonadotropins like FSH and LH is a method to identify and manage NOA [5].…”
Section: Introductionmentioning
confidence: 99%